Harmonizing Tradition and Progress: Organizational Management and Culture in Cambodia - Kounthiea, Syoluin (Journal of Asian Multicultural Research for Economy and Management Study, 2023)
The complicated dynamics of balancing tradition and advancement in Cambodian organizational administration are examined in this study. This study provides light on the fine line between tradition and progress by examining the effects of cultural factors on leadership styles, communication patterns, and adaption techniques. The results show relationships between transformational leadership and power distance, which illustrates how hierarchical cultural norms and leadership philosophies interact. The difficulties of open communication in a society that places a strong emphasis on harmony are further highlighted by the connection between collectivist communication styles and traditional values. Approaches to reconcile tradition and progress include gradual integration and cultural intelligence. This study emphasizes the value of context-sensitive techniques through a detailed comparison with prior studies. In the end, this study provides guidance for businesses negotiating the complex terrain of cultural dynamics, opening the route for peaceful development in a Cambodian setting.